Análise do valor adicionado gerado pelas empresas listadas no novo mercado BOVESPA e sua relação com o PIB nacional - Arraes, Eduardo (2014)
ln this work we analyze the consolidated, from the year 2012, Value Statement (VAS) of 132 business entities listed on Stock, Commodities and Futures Exchange- BMF & BOVESPA, part a specific segment named Novo Mercado BOVESP/ (NMB), who voluntarily brings together companies compromised with to apply the principles of corporate Governance, this segment was chosen for the accuracy of the regulation regarding transparency in corporate information. Were analyzed the Added Value generated by each segment and subsidiary group of companies separated by economic sector, the information found were confronted with the Brazilian Accounting Standard CPC 09. The results have reconciled to the methodology for ca1culatingand were compared with 2012 National GDP, were established a parallel between t1:1etwo calculation methodologies and ratio of the segment relevance on the national scenery. The VAS for its accounting approach, proved to be effidel1tand potentially important serve as a basis for decision-making of various social segments, including the government, which could use is as a data source for public policy of fomentation incentives.